Laser therapy for genitourinary syndrome of menopause: systematic review and meta-analysis of randomized controlled trial - Lisieux de Lourdes Martins Nóbrega Pessoa; Amaxsell Thiago Barros de Souza; Ayane Cristine Alves Sarmento; Ana Paula Ferreira Costa; Isis Kelly dos Santos; Eduardo Pereira de Azevedo; Kleyton Santos de Medeiros; Ana Katherine Gonçalves; Ricardo Ney Cobucci (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2024)
Abstract Objective: This meta-analysis of randomized controlled trials (RCTs) aimed to update evidence on the effectiveness and safety of laser therapy for treating genitourinary syndrome of menopause (GSM). Data sources: Manuscripts published until May 2023 were systematically searched in PubMed; Embase; Scopus; Web of Science; CENTRAL; CINAHL; and clinical trial databases (www.trialscentral.org, www.controlled-trials.com, and clinicaltrials.gov), with no language and year of publication restriction. Studies selection: RCTs with women diagnosed with GSM, and the intervention was vaginal laser therapy (CO2-laser or Er: YAG-laser) comparing with placebo (sham therapy), no treatment or vaginal estrogen therapy. Data collection: Two authors evaluated the publications for inclusion based on the title and abstract, followed by reviewing the relevant full-text articles. Disagreements during the review process were addressed by consensus, with the involvement of a third author. Data synthesis: Twelve RCTs, representing a total of 5147 participants, were included in this review. Vaginal health index (VHI) significantly improved in the carbon dioxide laser (CO2-laser) therapy group (MD=2.21; 95% CI=1.25 to 3.16), while dyspareunia (MD=−0.85; 95% CI=−1.59 to −0.10), dryness (MD=−0.62; 95% CI=−1.12 to −0.12) and burning (MD= −0.64; 95% CI=−1.28 to −0.01) decreased. No serious adverse effects were reported. Conclusion: CO2-laser increases VHI score and decreases dyspareunia, dryness and burning, especially when compared to sham-laser. However, the certainty of the evidence is low, thus preventing the recommendation of laser therapy for GSM management.